1997
DOI: 10.1090/s0002-9947-97-01814-x
|View full text |Cite
|
Sign up to set email alerts
|

Frobenius extensions of subalgebras of Hopf algebras

Abstract: Abstract. We consider when extensions S ⊂ R of subalgebras of a Hopf algebra are β-Frobenius, that is Frobenius of the second kind. Given a Hopf algebra H, we show that when S ⊂ R are Hopf algebras in the Yetter-Drinfeld category for H, the extension is β-Frobenius provided R is finite over S and the extension of biproducts S H ⊂ R H is cleft.More generally we give conditions for an extension to be β-Frobenius; in particular we study extensions of integral type, and consider when the Frobenius property is inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…Frobenius-type properties of extensions of Hopf algebras and of related algebras have been studied extensively; see, e.g., [Sch92, Doi97, FMS97, Kad99, KS01, KS02]. Fischman, Montgomery and Schneider [FMS97] showed that the Frobenius property of an extension of finite-dimensional Hopf algebras is controlled by their modular functions. The aim of this paper is to formulate and prove a generalization of their result in the setting of finite tensor categories, a class of tensor categories including the representation category of a finite-dimensional Hopf algebra.…”
Section: Introductionmentioning
confidence: 99%
“…Frobenius-type properties of extensions of Hopf algebras and of related algebras have been studied extensively; see, e.g., [Sch92, Doi97, FMS97, Kad99, KS01, KS02]. Fischman, Montgomery and Schneider [FMS97] showed that the Frobenius property of an extension of finite-dimensional Hopf algebras is controlled by their modular functions. The aim of this paper is to formulate and prove a generalization of their result in the setting of finite tensor categories, a class of tensor categories including the representation category of a finite-dimensional Hopf algebra.…”
Section: Introductionmentioning
confidence: 99%
“…, θ n ] we have gldim gr(U (L + )) = n = dim L + . By[6, Corollary 6.3] Λ is a Frobenius algebra; hence injdim gr(U) gr(U ) =n = dim L + as gr(U ) ∼ = Λ γ [θ 1 , θ 2 , . .…”
mentioning
confidence: 99%
“…Then U (L) is Auslander-Gorenstein and Cohen-Macaulay and thus has a quasi-Frobenius classical quotient ring.Proof. We have Λ is Auslander-Gorenstein and Cohen-Macaulay since Λ is a Frobenius algebra (see[6, Corollary 6.3]). As gr(U (L)) is an iterated Ore extension of Λ where each iteration is of the form R[x; σ], it follows from [10, Lemma (ii), p. 184] and[5, Theorem 4.2] that gr(U (L)) is Auslander-Gorenstein and Cohen-Macaulay.…”
mentioning
confidence: 99%
“…According to Lemma 5.3 and the proof of [23,Theorem 4.3], we obtain cx u >0 q (g) (C) = cx u ≥0 q (g) (C) ≥ 3 unless r = 1. Since u >0 q (g) is a Yetter-Drinfeld Hopf algebra over the group algebra C[(Z/ℓZ) r ], u >0 q (g) is a Frobenius algebra (see [24,Corollary 5.8] or [43, Proposition 2.10(3)]) and therefore self-injective. Thus, if r ≥ 2, Theorem 2.1 in conjunction with Corollary 5.2 implies that u >0 q (g) is wild.…”
Section: Let U ≥0mentioning
confidence: 99%
“…By the Krull-Remak-Schmidt Theorem, R ∼ = R * as R-modules, and so R is Frobenius. (For a proof in a much more general context, see [24,Corollary 5.8] or [43,Proposition 2.10(3)]. ) Since R is Frobenius, it is self-injective and the result now follows from Theorem 2.1 by choosing the block in which an indecomposable summand of M of complexity at least 3 lies.…”
Section: The Last Space Extmentioning
confidence: 99%